Die Entwicklung von epistemischer Wachsamkeit und epistemischem Vertrauen über die Lebensspanne: Perspektive aus der empirischen Forschung zum selbstregulierenden sozialen Lernen - Talia, Alessandro; Kling, Laura; Taubner, Svenja (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2024)
SUMMARY - - The Development of Epistemic Vigilance and Epistemic Trust Across the Lifespan: Perspectives from Empirical Research on Self-Regulatory Social Learning This article examines what we know about the development of epistemic vigilance and epistemic trust between early infancy and adolescence.With this brief review, we intend to help put into perspective the hypotheses advanced by Fonagy and his colleagues within the socio-epistemic theory of psychopathology, according to which psychopathology reflects a closure to interpersonal communication resulting from unfavorable learning experiences in early development. Here, we will discuss how children become sensitive to overt interpersonal communication, and what cognitive skills underpin such sensitivity. Next, we shall discuss the empirical evidence that children in the second year of life already possess a rudimentary capacity for epistemic vigilance: they seem to evaluate the competence of different adult informants and appear to seek information and learn from adults based on such evaluations. Third, we will outline studies showing that in the third year of life children appear to increasingly trust ostensive communication, up to the point of becoming (at least apparently) less sensitive to the possibility of being misinformed or deceived. Finally, we will discuss how, between late childhood and adolescence, children first learn to distinguish lies, then irony, and increasingly engage in complex communication ecologies. Our review simultaneously supports the basic principles of the socio-epistemic theory of psychopathology and suggests that the theory needs further refinement of its ontogenetic predictions.